Nasalização regressiva heterossilábica (NRH) da vogal /a/ acentuada em PE - Lao, Shanyi; Rodrigues, Celeste; Brissos, Fernando (Revista da Associação Portuguesa de Linguística, 2020)
According to the autosegmental model adopted by Mateus & Andrade (2000), the nasal vowel in Portuguese, in words such as cinco, lã and campo, is a phonetic form derived from a phonological oral vowel plus a nasal autosegment N in the same syllable. However, we can also notice the nasalization in words such as cãma, cẽna and cũnha in Portuguese, although not often in the standard language. This phenomenon is an heterosyllabic regressive nasalization (NRH), in which the nasal consonant of the onset nasalizes the previous vowel. In Brazilian Portuguese, there are more studies related to NRH than in European Portuguese and most of them treat it as a phonetic phenomenon (Câmara Jr., 1970; Battisti, 1997; Botelho, 2007). Moraes & Wetzels (1992) find NRH more frequently in the stressed syllable and with the palatal consonant /ɲ/, but its frequency varies in different dialects. Therefore, this paper aims to analyze the variation of NRH in Mainland Portugal and the phonological processes that go together with it, focusing particularly on the structure /a/[+ac] .C[+nas] (/m/, /n/, /ɲ/). We collected occurrences that contain the target structure from the corpus Linguistic-Ethnographic Atlas of Portugal and Galicia and our analysis is based on the phonetic transcriptions performed by CLUL dialectologists. By calculating the percentage of NRH in each locality and making dialectal maps, the results show that: i) NRH can be found almost throughout the entire territory; ii) it has a greater frequency in Northwest (mainly with the consonant /ɲ/), Beira Baixa, Alentejo, and Algarve; iii) multiple phenomena transform the phonological segments into different phonetic shapes; iv) in a diachronic analysis, the changing path of /a/ in Portuguese in this structure is: [a] → [ã] → [ɐ̃]→ [ɐ], which shows that the elevation of /a/ follows the NRH. Dialects, then, choose between one of these phonetic variants.